A tour of the Library of Congress - Cummins, Jim.; Library of Congress. Information Office (Washington, D.C. Information Office, Library of Congress)
An introduction of the Library of Congress showing its organization, resources and library services.
VHS
Narrated by Patrick Blake, editor, Tara Kelly.
Keywords: Library of Congress; Library science